Monitoring, Evaluation and Learning in NGO Advocacy - Findings from Comparative Policy Advocacy MEL Review Project - Coe, Jim; Majot, Juliette (ODI and Oxfam, 2013)
For organizations committed to social change, advocacy often figures as a crucial strategic element. How to assess effectiveness in advocacy is, therefore, important. The usefulness of Monitoring, Evaluation and Learning (MEL) in advocacy are subject to much current debate. Advocacy staff, MEL professionals, senior managers, the funding community, and stakeholders of all kinds are searching for ways to improve practices – and thus their odds of success – in complex and contested advocacy environments. This study considers what a selection of leading advocacy organizations are doing in practice. We set out to identify existing practice and emergent trends in advocacy-related MEL practice, to explore current challenges and innovations. The study presents perceptions of how MEL contributes to advocacy effectiveness, and reviews the resources and structures dedicated to MEL.

Miradi Measures Dashboard Demo - Salzer, D (2013)
Live demonstration (view in HD) of a new online measures dashboard site (http://miradi.sitkatech.com) that allows users of the Miradi Adaptive Management software (http://miradi.org) to share the progress they are making towards achieving their desired results

Outcome Measurement in Local Governance Programmes: a Power Dimension - McGee, Rosemary; Pettit, Jethro (WIP Paper, 2013)

Utilization-Focused Evaluation (U-FE) Checklist - Patton, Michael Quinn (Evaluation Checklists Projects, 2013)
Utilization-Focused Evaluation begins with the premise that evaluations should be judged by their utility and actual use; therefore, evaluators should facilitate the evaluation process and design any evaluation with careful consideration of how everything that is done, from beginning to end, will affect use. Use concerns how real people in the real world apply evaluation findings and experience and learn from the evaluation process. The checklist is based on Essentials of Utilization-Focused Evaluation (Patton, 2012, Sage Publications). All references in the checklist to exhibits and menus refer to this book. Step 1 Assess and build program and organizational readiness for utilization-focused evaluation. Step 2 Assess and enhance evaluator readiness and competence to undertake a utilizationfocused evaluation. Step 3 Identify, organize, and engage primary intended users. Step 4 Conduct situation analysis with primary intended users Step 5 Identify primary intended uses by establishing the evaluation’s priority purposes. Step 6 Consider and build in process uses if appropriate. Step 7 Focus priority evaluation questions. Step 8 Check that fundamental areas for evaluation inquiry are being adequately addressed. Step 9 Determine what intervention model or theory of change is being evaluated. Step 10 Negotiate appropriate methods to generate credible findings and support intended use by intended users. Step 11 Make sure intended users understand potential controversies about methods and their implications. Step 12 Simulate use of findings. Step 13 Gather data with ongoing attention to use. Step 14 Organize and present the data for use by primary intended users. Step 15 Prepare an evaluation report to facilitate use and disseminate significant findings to expand influence. Step 16 Follow up with primary intended users to facilitate and enhance use. Step 17 Metaevaluation of use: Be accountable, learn, and improve

It's All About MeE: Using Structured Experiential Learning (“e”) to Crawl the Design Space - Pritchett, Lant; Samji, Salimah; Hammer, Jeffrey (Working Paper 322, 2013)
This paper argues that within-project variations in design can serve as their own counterfactual, reducing the incremental cost of evaluation and increasing the direct usefulness of evaluation to implementing agencies. It suggests combining monitoring (‘M’), structured experiential learning (‘e’), and evaluation (‘E’) so as to facilitate innovation and organisational capability building while also providing accountability …

Complexity-Aware Monitoring - Britt, Heather; Patsalides, Melissa (Briefing on USAID's Discussion Note, 2013)

Outcome mapping for health system integration - Tsasis, Peter; Evans, Jenna; Forrest, David; Jones, Richard Keith (Journal of Multidisciplinary Healthcare, 2013)
Health systems around the world are implementing integrated care strategies to improve quality, reduce or maintain costs, and improve the patient experience. Yet few practical tools exist to aid leaders and managers in building the prerequisites to integrated care, namely a shared vision, clear roles and responsibilities, and a common understanding of how the vision will be realized. Outcome mapping may facilitate stakeholder alignment on the vision, roles, and processes of integrated care delivery via participative and focused dialogue among diverse stakeholders on desired outcomes and enabling actions. In this paper, we describe an outcome-mapping exercise we conducted at a Local Health Integration Network in Ontario, Canada, using consensus development conferences. Our preliminary findings suggest that outcome mapping may help stakeholders make sense of a complex system and foster collaborative capital, a resource that can support information sharing, trust, and coordinated change toward integration across organizational and professional boundaries. Drawing from the theoretical perspectives of complex adaptive systems and collaborative capital, we also outline recommendations for future outcome-mapping exercises. In particular, we emphasize the potential for outcome mapping to be used as a tool not only for identifying and linking strategic outcomes and actions, but also for studying the boundaries, gaps, and ties that characterize social networks across the continuum of care.